Procedural Mechanisms for Confronting International Terrorism through Preventive Measures - Makki Majeed , Assist. Lect . Marwah; Mohammad Ibrahim, Prof.Dr. Moussa (Basra studies journal, 2025)
This study examines the issue of confronting international terrorism and the preventive mechanisms designed to counter it، with a particular focus on the essential balance between security and the protection of human rights. It reveals the shortcomings present in many international conventions، especially their failure to clearly define fundamental concepts such as surveillance، privacy، and arbitrary interference. Moreover، some of the vague formulations in these conventions allow states to justify security measures under the pretext of “state security.” The study also highlights challenges arising from weak international coordination in intelligence sharing and tracking terrorist groups، which limits the effectiveness of preventive measures. It concludes that combating terrorism requires the development of both national and international legislation، strengthening judicial and intelligence cooperation among states، ensuring the integration of human rights protection into all procedures، and promoting awareness to prevent the exploitation of individuals in terrorist activities.